DETERMINANTS OF PURCHASE INTENTION OF HALAL SKINCARE PRODUCTS AMONG INDONESIA’S GENERATION Z - Fauziah, Fauziah; Muchtar, Ibnu Hasan; Sugiyarto, Wakhid; Imansah, Retno Kartini Savitaningrum; Suhanah, Suhanah; Muizzudin, Muizzudin (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
The 2014 Halal Products Guarantee Law requires products distributed in Indonesia to be halal certified. Skincare products are included in this law. However, halal skincare brands are still facing challenges in their positioning and are unable to identify how to encourage customers to buy. Although there is an increasing awareness towards the use of halal skincare among Indonesia’s Generation Z, the factors that might stimulus their purchase intention of halal skincare are perceived to be varied. Besides, there is a lack of well-established study on the role of religious belief as a predictor to Indonesia’s Generation Z consumers’ purchase intention. To address the gap, this study aims to propose a model to reveal the distinctive factors that influence the purchase intention of halal skincare among Generation Z in Indonesia. The population for this study consists of Generation Z consumers in Indonesia and the respondents are taken based on purposive sampling. A closed-ended questionnaire is employed for data collection from a sample of 250 respondents. The proposed model is tested with regression. This study discovers that the use of brand ambassador, halal logo, and promotion plays the important role in purchase intention. This study also finds which factor plays the most and the least important. This study recommends cosmetics companies to position their products based on the importance of the factors observed. It also suggests marketers to understand the right promotion strategy to be used in targeting the right market segment.